2018
DOI: 10.1111/ene.13805
|View full text |Cite
|
Sign up to set email alerts
|

Predicting responsiveness to fampridine in gait‐impaired patients with multiple sclerosis

Abstract: Initial walking impairment is a good predictor of therapeutic responsiveness to PR-fampridine. Valid predictors of patients' responsiveness to PR-fampridine are essential for patient stratification and optimization of multiple slcerosis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…KA group) were diagnosed with secondary progressing MS and revealed higher EDSS scores compared to non-responding patients. This is in line with previous findings reporting that PwMS with higher levels of functional disability show enhanced responsiveness to PR-fampridine compared to mildly impaired PwMS [24][25][26]. Superior positive drug responses in patients with severe MS-related impairments might be attributed to more pronounced axonal demyelination and neural damage in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…KA group) were diagnosed with secondary progressing MS and revealed higher EDSS scores compared to non-responding patients. This is in line with previous findings reporting that PwMS with higher levels of functional disability show enhanced responsiveness to PR-fampridine compared to mildly impaired PwMS [24][25][26]. Superior positive drug responses in patients with severe MS-related impairments might be attributed to more pronounced axonal demyelination and neural damage in these patients.…”
Section: Discussionsupporting
confidence: 92%
“…EDSS only weakly correlated with the outcome. In this study, reduced walking endurance as measured by the 6MWT was the best predictor of a good outcome with an accuracy of 80% [7]. In comparison, we found that EDSS correlated with improvement in T25wt; however, we did not test walking endurance, since we included patients with advanced gait impairment who were unable to complete the 6MWT.…”
Section: Discussionmentioning
confidence: 67%
“…The positive impact of fampridine on gait speed is now well established, but only 40% of patients are expected to experience a clinically meaningful improvement [15,21]. Proper selection of patients most likely to experience clinical benefits from fampridine has been the subject of rare dedicated studies [6][7][8]. It has been suggested that patients with more disability at baseline have the best outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations